Angular distribution of X-ray radiation by 500 MeV electrons in a tungsten crystal; Nuclear Instruments and Methods in Physics Research Section B: Beam Interactions with Materials and Atoms; Vol. 201, № 1 - Adishchev Yu. N. Yuri Nikolaevich; Arishev S. N.; Vnukov A. V.; Vukolov A. V. Artem Vladimirovich; Potylitsyn A. P. Alexander Petrovich; Kuznetsov S. I. Sergey Ivanovich; Kalinin B. N.; Kubankin A. S. Aleksandr Sergeevich; Nasonov N.; Zabaev V. N. Viktor Nikolaevich; Kaplin V. V. Valeriy Viktorovich; Uglov S. R. Sergey Romanovich (2003, 2003)
Title screen